The Problem Of Evil For Buddhists: Developing Transcendental Responses - McNabb, Tyler Dalton (AGATHEOS – European Journal for Philosophy of Religion, 2024)
Many Buddhists tend to think that the world is overall, a good state of affairs, and that life is worth living. However, Yujin Nagasawa points out that there is a mismatch between the positive value one puts on the world and the Buddhist's metaphysics. Buddhism endorses the impermanence thesis which roughly states that all things exist only momentarily. And it’s the impermanent nature of reality that, at least in part, leads to significant suffering in the world. If impermanence is a fundamental feature to reality, and, if suffering is primarily linked to the impermanent nature of reality, how can one consistently give an optimistic assessment of the value of the world? In this paper, I come to the aid of the Buddhist and point to how she might develop her own response to this problem.